Characterization, efficacy and toxicity potential of chlorogenic acid and protocatechuic acid-layered double hydroxide nanohybrids on a cancer model - Abd Gani, Shafinaz (2018)
Cancer is the second leading cause of morbidity and mortality in the world. Due to the limitations and side effects of most available anticancer therapy, there is an urgent need to develop new anticancer agents. Nanoparticles sciences have opened up a new world of opportunities for development of efficient therapeutic treatment for cancer therapy. Recent studies demonstrate that layered double hydroxide (LDH) hold a considerable promise as potential anticancer nanocarrier. In addition to the novel size and shape, LDH exhibit a pH-sensitive controlled-release-property. The property of LDH could allow increased of cytotoxic effects on cancer cells. The present project is aimed to explore the efficacy and toxicity of layered double hydroxide nanocomposite as a vector for cancer therapy. For this reason, a nanohybridization process was conducted to synthesize protocatechuic acid (PCA) and chlorogenic acid (CA) intercalated to inorganic layered double hydroxide (LDH), namely zinc-aluminum and magnesium aluminium LDH. The two compounds are of polyphenolic groups reported to have anticancer activities. The nanocomposites have sandwich-like structure which allows sustained, continuous and slow release ability with increase cellular uptake compared to conventional drug delivery system, proven to be biocompatible with less toxicity in most cases. The synthesis process of the nanocomposites was via ion exchange and direct coprecipitation method. The physicochemical parameters such as size, charge, drug loading capacity and controlled release profile of these compounds were thoroughly characterized. A screening process of the synthesized nanocomposites on various cancer cells versus normal cells was conducted using mitochondrial dehydrogenase activity assay (MTT assay). The tested nanocomposites were observed to preserve the viability of all normal cells tested within the tested range of concentration and duration. Some exert cytotoxicity effect on the cancer cells. Protocatechuic acid-zinc/aluminium layered double hydroxide synthesized via ion exchange method (PCA-ZnAl-IEX) showed the best cytotoxicity towards HepG2 cells with the lowest IC50 20.5μg/ml after 72 hours of treatment period. Thus, PCA-ZnAl-IEX and HepG2 cells were used in the subsequent studies. To test the potential chronic toxicity of PCA-ZnAl-IEX in in vitro level, clonogenic assay was tested on HepG2 cells. Acridine orange/ propidium iodide (AO/PI) dual staining methods then, was used to detect morphological changes, including possible induction of apoptosis and necrosis. The intracellular uptake of PCA-ZnAl-IEX compared to PCA alone was investigated in HepG2 using High Performance Liquid Chromatography (HPLC). The uptake of PCA from PCA-ZnAl-IEX by HepG2 was significantly higher compared to PCA alone when incubated with HepG2 cells. To understand the underlying efficacy and toxicity of PCA-ZnAl-IEX in hepatocellular carcinoma (HCC), BALB/c mice was induced with diethylnitrosamine (DEN) and phenobarbital (PB). After confirmation of significant induction of HCC, selected dose of PCA-ZnAl-IEX was administered for 4 weeks. Liver was removed for histological, biochemical and protein expression analysis to compare the differences between PCA-ZnAl-IEX and relevant controls. It was observed that PCA-ZnAl-IEX was able to attenuate liver damage in the inflicted HCC animal model. Possible enhancement of apoptotic pathways by PCA-ZnAl-IEX may have hindered the advancement of HCC in the mice model. The results obtained from this study shows that the nanocomposite successfully to increase the bioavailability of bioactive compound into the cancer cells compared to the pure counterpart. It also possessed an increase specificity of LDH nanocomposite on cancer cells consequently reduce toxicity seen on normal cells in both of in vitro and in vivo studies.